WHITE RATS THYROID GLAND MICRO- AND ULTRA-MICROSCOPIC CHANGES 7 DAYS AFTER THE EXPERIMENTAL THERMAL INJURY IN CONDITIONS OF PHYSIOLOGICAL SALINE ADMINISTRATION - Tiron, O.I.; Stoyanov, O.M.; Kuvshinova, I.I.; Markova, O.O.; Liashevska, O.O.; Volokhova, G.O.; Atmazhov, I.D. (World of Medicine and Biology, 2023)
The purpose of the study was to determine the microscopic and ultrastructural changes in the experimental animals’ thyroid gland 7 days after simulated thermal skin injury. Microscopic studies have established the intrathyroid changes of different degrees and of a predominantly destructive nature in the follicles, thyrocytes, vessels and stroma 7 days after the thyroid gland experimental thermal injury. Micro- and ultra-microscopic studies of thyroid tissue 7 days after thermal damage of the body revealed expressed changes of the mainly destructive nature. Follicles of various sizes with intracellular swelling, the presence of swollen thyrocytes with a changed shape, oxyphilic cytoplasm and destructively changed intracellular organelles, pathological changes in the surrounding connective tissue and impaired blood supply - the established pathomorphological correlates showed the irreversibility of the detected histological changes. Physiological solution injection and attempts to restore the circulating blood volume proved the failure of thyroid burn pharmacocorrection. Therefore, the results of micro- and ultra-microscopic studies of the thyroid gland of animals under the specified conditions against the background of NaCl administration established the processes thyrocytes structure remodeling, the capillaries walls and stromal connective tissue remodeling with signs of their destruction and alteration, which indicates the organ functional activity worsening.